Magnetic Resonance Imaging as the Primary Imaging Modality in Children Presenting with Inflammatory Nontraumatic Atlantoaxial Rotatory Subluxation - Katharina J. Wenger; Elke Hattingen; Luciana Porto (MDPI AG, 2021)
Inflammatory nontraumatic atlantoaxial rotatory subluxation (AAS) in children is an often-missed diagnosis, especially in the early stages of disease. Abscess formation and spinal cord compression are serious risks that call for immediate surgical attention. Neither radiographs nor non-enhanced computed tomography (CT) images sufficiently indicate inflammatory processes. Magnetic resonance imaging (MRI) allows a thorough evaluation of paraspinal soft tissues, joints, and ligaments. In addition, it can show evidence of vertebral distraction and spinal cord compression. After conducting a scoping review of the literature, along with scientific and practical considerations, we outlined a standardized pediatric MRI protocol for suspected inflammatory nontraumatic AAS. We recommend contrast-enhanced MRI as the primary diagnostic imaging modality in children with signs of torticollis in combination with nasopharyngeal inflammatory or ear nose and throat (ENT) surgical history.